A Case of Mesh Erosion to the Sigmoid After Laparoscopic Sacrocolpopexy and a Literature Review of Mesh Related Complications. Issue 4 (July 2018) - Lin, Xiaoting; Du, Pei; Chen, Liquan; Gan, Yaping; Zhang, Xiaowei
Abstract : Abstract: Sacrocolpopexy has long been the preferred surgical procedure for the management of apical vaginal prolapse. The published literature regarding rectal mesh erosion after sacrocolpopexy includes only 6 cases in MEDLINE. We report a case of sigmoid vaginal fistula identified 4 years after laparoscopic sacrocolpopexy, along with an analysis of the follow-up of 140 patients over 12 months or more. Abstract : Sigmoid vaginal fistula after laparoscopic sacrocolpopexy is a rare but serious complication.